2013
DOI: 10.1378/chest.11-3031
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Critical Care Telemedicine Programs

Abstract: ICUs deliver focused care to critically ill patients; but despite advances in ICU care, mortality rates remain high and vary significantly. 1,2 There is an increased effort to improve patient outcomes by providing dedicated intensivist staffi ng in all ICUs and promoting adoption of evidence-based therapies. [3][4][5][6][7][8] Access to intensivists has been hampered by an array of factors, most notably the limited supply of intensivists, particularly for smaller hospitals and rural geographic regions. [9][10]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 33 publications
(59 reference statements)
1
56
0
Order By: Relevance
“…3 Additional research is needed to further delineate issues related to tele-ICU that specifically affect nursing practice. A recent systematic review 17 indicated that the cost of tele-ICU implementation is substantial and that the impact of these programs on hospital costs or profits is unclear. No information on costs related to tele-ICU nursing care or on alternative nurse staffing models is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additional research is needed to further delineate issues related to tele-ICU that specifically affect nursing practice. A recent systematic review 17 indicated that the cost of tele-ICU implementation is substantial and that the impact of these programs on hospital costs or profits is unclear. No information on costs related to tele-ICU nursing care or on alternative nurse staffing models is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that telemedicine has been used in several healthcare areas for improving outcomes, lowering costs, and heightening patient access to high levels of care. 5,6 Ours is a positive story of the value of tele-ICU technology in rendering critical care to a patient and validated the use of tele-ICU technology when donor organs are identified in a rural hospital that does not have a trauma unit or board-certified anesthesiologists. A remotely based critical care team can be networked with the bedside ICU team via state-of-the-art audiovisual communication and computer systems.…”
Section: Discussionmentioning
confidence: 99%
“…We estimate the costs of our intervention to be approximately $380,000 at start-up and approximately $900,000 annually, including hardware, staffing and administrative costs. These costs are substantially less than the costs of a full telemedicine program, which can exceed $3 million annually (23). Given the reductions in duration of mechanical ventilation we observed, the intervention is likely to have resulted in substantial cost savings (13), making this intervention budget neutral even under conservative assumptions.…”
Section: Discussionmentioning
confidence: 99%